2016
DOI: 10.3402/tellusa.v68.28393
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the value of larger ensembles in forecasting physical systems

Abstract: A B S T R A C T Ensemble simulation propagates a collection of initial states forward in time in a Monte Carlo fashion. Depending on the fidelity of the model and the properties of the initial ensemble, the goal of ensemble simulation can range from merely quantifying variations in the sensitivity of the model all the way to providing actionable probability forecasts of the future. Whatever the goal is, success depends on the properties of the ensemble, and there is a longstanding discussion in meteorology as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…To apply the logarithmic score, the pdf has been modelled by a Gaussian here, so that the score is equivalent to the Dawid–Sebastiani score, which has been shown to decrease asymptotically with ensemble size m as m −1 . Machete and Smith () examined a more general situation, in which a kernel density estimate allows different shapes of pdfs. It is an open question how such an approach will change the asymptotic convergence properties of the logarithmic score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To apply the logarithmic score, the pdf has been modelled by a Gaussian here, so that the score is equivalent to the Dawid–Sebastiani score, which has been shown to decrease asymptotically with ensemble size m as m −1 . Machete and Smith () examined a more general situation, in which a kernel density estimate allows different shapes of pdfs. It is an open question how such an approach will change the asymptotic convergence properties of the logarithmic score.…”
Section: Discussionmentioning
confidence: 99%
“…For an eight‐member ensemble, the DSS is about 0.2 nats larger than for a 50‐member ensemble. Machete and Smith () define a competitive advantage that depends on the difference in logarithmic scores as expfalse(normalΔLSfalse)1 when the logarithmic score LS is computed with the natural logarithm. The competitive advantage of using 50 instead of 8 members turns out to be about 30%.…”
Section: Convergence Of Probabilistic Skillmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrations have been performed between 1850 and 2005 with the aim of assessing the value of an ensemble experiment in determining to what extent a climate change signal can be separated from internal chaotic variability, but we do not address climate change directly by using future projections as in some studies. The model used in this study represents the observed internal variability sufficiently well and it can therefore be assumed that an ensemble of 100 members will be sufficient to separate the forced mode from the internal variability (Machete and Smith 2016). The distribution of trends in temperature and precipitation are compared with the observed trends and those from previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…The circuit was first introduced in [50] and later discussed in more detail in [51]. References [51] and [52] discuss different aspects of its predictability properties. The circuit is designed to produce output voltages that mimic the Moore-Spiegel [53] three-dimensional system of ordinary differential equations:…”
Section: A Nonlinear Circuitmentioning
confidence: 99%